Direct ink writing of programmable functional silicone‐based composites for 4D printing applications. Issue 4 (5th July 2022) - Lyu, Zhiyang; Koh, J. Justin; Lim, Gwendolyn J. H.; Zhang, Danwei; Xiong, Ting; Zhang, Lei; Liu, Siqi; Duan, Junfei; Ding, Jun; Wang, John; Wang, Jinlan; Chen, Yunfei; et al.
Abstract: Polydimethylsiloxane (PDMS) has been widely used in flexible electronics, soft robotics, and bioelectronics. However, the fabrication of PDMS‐based devices has mostly relied on conventional approaches, such as casting and molding, thereby limiting their potential. Here we fabricate PDMS‐based composites with programmable microstructures by direct ink writing and realize their practical functionalities of four‐dimensional (4D) printing. The mechanical, thermomechanical and magnetic properties of the three‐dimensional‐printed composites can be well tailored by using carbon, metal, or ceramic functional fillers. By taking advantage of the printable, flexible, and magnetic PDMS composites, we demonstrate new practical functionalities of 4D printing by designing programmable architectures, including magnetic‐field‐driven battery cases and patchworks, as well as arbitrary morphing ceramic structures. In particular, 4D‐printed batteries are constructed by PDMS‐based battery cases for the first time, which can be actuated via external magnetic field. This study broadens the paradigm of 4D printing for prospective applications, such as implant batteries, biomimetic engineering, and customized biomedical devices. Abstract : Three‐dimensional printable polydimethylsiloxane (PDMS)‐based composites with carbon, metal, and ceramic functional fillers are developed. The programmable architectures are designed by printing the PDMS‐based composites and demonstrated to present new practical functionalities of four‐dimensional (4D) printing, including magnetic‐field‐driven 4D‐printed batteries and patchwork with flip motion underwater, as well as arbitrary morphing ceramic architectures.